The Dynamics of Advice-Giving by Venture Capital Firms: Antecedents of Managerial Cognitive Effort - Gerasymenko,Violetta; Eggers,J.P. (Journal of Management, 2017)
This study investigates what leads managers to allocate constrained the cognitive effort towards new versus familiar aspects of a business. We explore this question in the context of venture capitalists’ (VCs) advice-giving to their portfolio companies on business topics on which they have advised other ventures in the past, versus on topics new to the VC that may be outside their areas of expertise. We use both demand-side (venture-driven) and supply-side (VC-driven) perspectives to build a novel theory about the antecedents of cognitive effort underlying advice-giving. By empirically testing our theory using a novel dataset, we find that both perspectives explain important aspects of advice-giving dynamics for VCs. This supports the idea that VCs, facing dynamic environments and capacity constraints, definitely respond to stimuli from ventures, but also that VCs change their behavior as they accumulate experience in ways that reflect expanding confidence in their ability to add value and concerns about overextension of their efforts, depending on the valence of VC experience. Our findings provide novel insights to the antecedents of cognitive effort and to research on the VC-venture relationship by exploring the dynamics of how these advice-giving relationships evolve over time as VCs gain experience.
Keywords: Strategy & Entrepreneurship